Do Halal Literacy, Religiosity, and Legal Compliance Affect the Motivation of Applying for Halal Product Certification? - Sholeh, Khabib; Afif Zaerofi; Yono Haryono (Institut Agama Islam Negeri Madura, 2024)
The enactment of regulations regarding the obligation to guarantee halal products in Indonesia according to Law Number 33 2014 is mandatory and binds for SMEs owners to have halal guarantees for all products that are offered. However, the number of Indonesian SMEs that have been halal-certified remains very low and far from their potential. The purpose of this study was to analyze the effect of the level of literacy, religiosity, and legal compliance of SMEs owners on halal product guarantee regulations using a quantitative approach with a research instrument in the form of a questionnaire distributed to SMEs owners in Depok. This study used a purposive sampling technique and obtained as many as 152 food SMEs that had not been halal certified. The results of this study show that halal literacy and religiosity influence the motivation of SMEs owners to apply for halal certifications. There are still SMEs owners who do not know or understand the rules and requirements for applying for halal certification. Legal compliance has no influence on SME owners’ motivation to apply for halal product certification. The majority of respondents complied with business regulations but did not have halal certification. The results of this study are expected to contribute to the implementation of halal certification policies and growth of the halal industry in Indonesia.